Relationship between obesity with symptoms and findings of obstructive sleep apnea syndrome - Ünlü, Murat; İriz, Ayşe and Ayçiçek Doğan, Berçem and Seçil Kayalı Dinç, A. and Dursun, Engin and Eryılmaz, Adil and Acar, Aydın (ENT Updates, 2014)
Objective: To evaluate the effect of obesity on obstructive sleep apnea syndrome (OSAS) by means of objective and subjective data.. Methods: A total of 70 patients were divided into obese (n=38; BMI>35 kg/m2 ) and non-obese patient groups (n=32; BMI<30 kg/m2 ). The Epworth sleepiness scale scores, modified Mallampati index scores, levels of obstruction in the oropharynx and soft palate, neck circumference and polysomnography findings between two groups were compared. Results: Obese patients had an average Mallampati score of Class III while the non-obese study participants had an average score of Class II, with a statistically significant intergroup difference. In Muller’s maneuver, the levels of obstruction in both the soft palate and oropharynx were higher in the obese patients with a statistically significant difference between two groups. When polysomnography results were examined, the average apnea-hypopnea index (AHI) score was determined to be 22.5 in the obese and 6.4 in the non-obese groups, respectively. Furthermore, average scores of rapid eye movement (REM) AHI in the non-obese and obese patients were 4.6 and 17.2 with a statistically significant difference between the groups. The average lowest oxygen saturation was 75.5% in the obese and 88% in the non-obese group, which represented a statistically significant difference between groups. In the obese group, the number of patients with REM-dependent OSAS was higher than in the nonobese group which attained a level of statistical significance. Conclusion: Our study indicated that obesity increases the severity of OSAS, in part due to significant narrowing of the airway at the level of the soft palate and oropharynx. Additionally, our study has shown that the risk of supine position-dependent OSAS and especially REM-dependent OSAS were notably higher in obese patients.